Exploring Central Government Assistance for Urban Public Transport: A Mobility-Based Social Exclusion Perspective. Issue 1 (2016) - Li, Ye; Deng, Haopeng
China's insufficient assistance by the central government for public transport is largely due to the traditional system-based policy perspective, which usually overemphasizes public transport as a municipal infrastructure rather than as a mechanism for social inclusion. Within this context, a new insight into the rationale and equality of central government assistance for the country's public transport service is offered. By using a social exclusion approach, this study highlighted the obligation of the central government to adhere to mobility for every citizen so as to mitigate mobility-based social exclusion. On this premise, it is argued that urban public transport necessarily merits financial assistance given its primary function as a safety net of affordable mobility for all citizens. Furthermore, a method for policy makers to estimate the amount of central government assistance is established that could ensure that all urban residents are above the basic mobility line. With reference to a case study, the amount of central government assistance for public transport is estimated to be ¥14.8 billion annually (¥1 = 0.148 in 2010); this estimate is considered to be the proper level of financing compared with other central government transfer payments. With regard to the allocation of this fiscal assistance, the paper proposes various simple criteria and formulas, the basis of which are the gaps between need and provision in public transport service as measured by the index of disparity between needs and provision.